The Role Of School Sport In Realizing The Social Peace Of Middle School Pupils - Barkati Nasereddine . (sports creativity, 2025)
Abstract: the study aimed at knowing the role of school sports in achieving the social peace according to pupils. It aimed also at knowing the social sports role in achieving the social peace from the teachers, the supervisors and the parents’ point of view. The researcher used the descriptive method which fits the nature of the study through using the questionnaire as a data gathering tool this later which was distributed on a sample of tree categories that are: pupils, teachers and supervisors and parents. It was composed of 100 pupils (males and females), 15 teachers and supervisors, and 15 parents. After applying the study’ tool, it shows the following: _ practicing schools sports activities is a tool to achieve school peace. _ practicing the school sports activities inside the educational institutions is a way of achieving social peace and stability. _ practicing school sports activities is a means of adjusting the pupils’ behavior in parallel with social needs. _ the sports competitions inside the schools and the educational institutions is a means of enhancing peace between the schools ‘pupils. The key words: school sports, cial peace, pupils, middle school stage